Strategi Kebiasaan Sehari-hari untuk Menanamkan Nilai-Nilai Akhlak Islam pada Masa Kanak-kanak - Nur Afina; Wahyu Mulyadi; Nurdiniawati Nurdiniawati (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the implementation of daily habituation strategies in internalizing Islamic moral values among early childhood learners at PAUD KB Sehat Mpili. It emphasizes the importance of strengthening character education through consistent and structured practices from an early age. A descriptive qualitative approach was used, with data collected through participatory observation, in-depth interviews, and document analysis involving the principal and teachers. The findings show that activities such as greeting practices, routine prayers, time discipline, responsibility-based tasks, and guided social interactions contribute to the development of moral behaviors, including politeness, empathy, responsibility, and adherence to routines. These processes are supported by teacher role modeling and positive reinforcement, enabling gradual value internalization through repeated experiences. Internalization is understood as a continuous process in which children adopt values in daily learning contexts. The study reveals that habituation does not directly determine outcomes but plays a significant role in shaping children’s moral behavior patterns. Its novelty lies in viewing habituation as part of an integrated pedagogical system that connects daily practices, teacher modeling, and value reinforcement, contributing to early childhood character education.